The experience of cranioplasty outcome, management and its complication in neurosurgery - Kalhoro , Aurangzeb; Lal Rehman; Panezai , Abdul Samad; Sher Hassan; Farrukh Javeed (International Journal of Endorsing Health Science Research, 2022)
Background: Head trauma is the most common case encountered in neurosurgery, and it is on the rise daily; head trauma sometimes requires the removal of skull bone which leads to another set of complications and associated issues related to cranioplasty. The study's objective was to share the single-center tertiary care hospital experience of cranioplasty, including outcomes, management, and associated complications. Methodology: Patients who underwent reconstructive cranioplasty at the study site from 2015-2020 were examined in this retrospective descriptive study conducted at the department of neurosurgery, Jinnah postgraduate medical center, Karachi. Patients aged 18 to 60 years were considered for cranioplasty procedures, preceded by the decompressive post-craniotomy for brain trauma, skull fracture, intractable intracranial hypertension, brain tumor, and infected post-craniotomy bone flaps were included in the study. Results: A total of 68 patients who presented to the study center with cranial defects were included in this study. The frequent cause of cranioplasty was the traumatic injury to the brain in 38(55.88%), followed by brain tumors in 321(0.4%) and cerebrovascular injury in 9(13.23%) cases. In our study, no patient required more than one cranial procedure. The anatomical regional wise division of defects was temporal 29(42.64%), frontal 15(22%), and parietal 24(35.39%). Conclusion: Indications for cranioplasty, type of bone graft, associated comorbidities, and complications have been addressed that are potentially preventable.